Intelligent playgrounds: Measuring and affecting social inclusion in schools - Lyra, Olga; Karapanos, Evangelos; Kostakos, Vassilis (My University, 2011)
Equal access to education has recently been declared by the United Nations a basic human right [14]. However, despite the substantial attention given to inclusive education in recent years, researchers have criticized a lack of empirical evidence on how exclusion is manifested in student behavior. Recent development in sensor technology and social network analysis techniques can provide a new perspective to the impact of educational practices through the measurement of students' social interactions. In this paper we outline our research agenda that aims at a) measuring the current stand as well as the impact of inclusive educational interventions using sensor technology and sociometric analysis, and b) challenging pupils' perceptions of diversity with the aim of eliminating discriminatory behaviors in primary schools using persuasive games.
Keywords: Inclusive education; Persuasive games; Social networks